A system dynamics approach for poultry operation to achieve additional benefits - Shamsuddoha, M.; Quaddus, Mohammed; Klass, D. (2013)
Poultry generates various wastes such as litter, reject and broken eggs, intestines, waste feeds, feather and culled birds. Most of the farm owners do not utlize these wastes for further by-product generation. Without profitability, farmers do not reuse their waste. System dynamics along with simulation is a tool that can be used to forecast the feasibility of waste and by-products generation. In this paper, we present a poultry model grounded on system dynamics to determine the interaction among factors in the system using a software package, Vensim. A case poultry industy in the city of Chittagong, Bangladesh was selected to conduct the study. The objectives of this paper are twofold. First, it develops a qualitative model on poultry operation. Second, it constructs a simulation model to explore possible opportunities available by recycling poultry wastes within the same poultry operation. © 2013 IEEE.